Fatigue behaviour of WC-Co hard metal under stress ratio and effectively loaded volume relevant to metalworking tool failure. (April 2019) - Klünsner, T.; Jonke, M.; Supancic, P.; Gettinger, C.; Krobath, M.; Lube, T.; Marsoner, S.; Glätzle, J.
Abstract: WC-Co hard metals have proven to be excellent tool materials capable of coping with the elevated cyclic load levels that arise in e.g. metalworking tool application. The design of cyclically loaded tools requires reliable information on the fatigue behaviour of hard metals, also as a function of the acting mean stress. Since hard metals show defect controlled fracture behaviour, the nature of defects and their size distribution in the volume of given loaded structures is relevant to their fatigue behaviour. The concept of effectively loaded volume V eff allows for the comparison of the fracture probability of loaded structures with different kinds of stress distributions. To date, V eff of laboratory test setups and metalworking tools and its influence on the fatigue behaviour was not considered in the respective design processes. Instrumented milling experiments in combination with finite element based load analysis were used in the current work to provide information on typical values of stress ratio and V eff for end milling tools. A newly developed non-conventional type of a six point bending test setup was designed to induce values of V eff and mean stress which were found to be representative for the metalworking tool. The shape of the used central specimen support structures was designed to avoid contact damage to the specimen at the sites of load transfer. The knowledge-based design of the six point bending test setup assures that a region of the hard metal's bimodal defect size distribution is probed that leads to fatigue limits relevant to the failure behaviour of end milling tools. Highlights: Effectively loaded volume V eff of end milling tools is about 0.1 mm 3 . New kind of 6 point bending test setup for fatigue testing under R = −1 and V eff < 1 mm 3 . Test setup prevents influence of load application on observed fatigue behaviour. Test setup probes region of defect size distribution relevant to tool failure. Scatter of cycles to failure for small V eff far smaller than for larger values of V eff .